Ineffectiveness of Recombinant Interferon-βserine Nasal Drops for Prophylaxis of Natural Colds - Sperber, Steven J.; Levine, Paul A.; Sorrentino, James V.; Riker, Donald K.; Hayden, Frederick G. (The Journal of infectious diseases, 1989)
Two randomized, double-blind, placebo-controlled trials during early autumn of 1986 and 1987 evaluated the efficacy and tolerance of recombinant interferon-βserine (rIFN-βser) nasal drops for prevention of natural rhinovirus colds. In 1986, 9 × 106 units of rIFN-βser (139 subjects) or placebo (157) were adminstered once daily except Sundays for 4 w. Rhinovirus colds occurred in 2.8% of rIFN-βser recipients and 6.0% of placebo recipients during the treatment period (52% reduction, P = .3). In 1987, 24 × 106 units of rIFN-βser (186) or placebo (197) were given daily for 25 consecutive days. Rhinovirus colds developed in 6.3% of rIFN-βser recipients and 5.3% of placebo recipients. In each study, illness frequency and number of days with subjective colds did not differ between the groups. Recipients of nasal drops of rIFN-βser at either dosage did not differ in tolerance from placebo recipients. The lack of both prophylactic efficacy and nasal toxicity are in contrast to prior observations with nasal sprays of rIFN-α2b.